2002
DOI: 10.1038/sj.gt.3301591
|View full text |Cite
|
Sign up to set email alerts
|

Brain engraftment of autologous macrophages transduced with a lentiviral flap vector: an approach to complement brain dysfunctions

Abstract: Transplantation of ex vivo gene-corrected autologous cells represents an attractive therapeutic approach for brain diseases. Among the cells of the central nervous system, brain macrophages are promising candidates due to their role in tissue homeostasis and their implication in several neurological diseases. Up to now, gene transfer into macrophages has proven difficult by most currently available gene delivery methods. We describe herein, an efficient transduction of rat bone marrow-derived and brain macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…Unfortunately, most classes of viral vector have proven to be poor agents to transfer genes into microglia and other myeloid lineages. One possible exception are vectors derived from complex lentiviruses, such as HIV, 35,36 which naturally target this cell type. However, most such vectors also carry significant stretches of native viral coding sequence, because their packaging signals are embedded within viral open reading frames.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most classes of viral vector have proven to be poor agents to transfer genes into microglia and other myeloid lineages. One possible exception are vectors derived from complex lentiviruses, such as HIV, 35,36 which naturally target this cell type. However, most such vectors also carry significant stretches of native viral coding sequence, because their packaging signals are embedded within viral open reading frames.…”
Section: Discussionmentioning
confidence: 99%
“…Among the cell types which are susceptible to HIV-1-based vectors are hematopoietic stem cells [1][2][3][4][5][6][7] and monocytes/macrophages [8][9][10][11][12][13] which represent important targets for human gene therapy [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the observation that monomyeloic cells are targets of the M-tropic strains of HIV, several groups have used lentiviral vectors successfully to introduce transgenes into macrophages (Burke et al, 2002). Two preliminary studies reported the feasibility of microglial transduction by lentiviruses (Wrzesinski et al, 2000;Mordelet et al, 2002), but no efficiencies or other details for microglial transduction were reported.…”
Section: Introductionmentioning
confidence: 99%